Dom Miśnia rodu Derów herbu Doliwa - Kruszewski, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
For the third time the author tackles the problem of the Dern-Dera family, and once again he corrects himself, this time presenting his final position. The article is devoted to the house of Meissen of the Dera family. The author demonstrates that the family did not come from Diera but in the three previous generations referred to itself as of Zehren and, earlier still, de Misna. Its true founder was Hoierus de Misna (floruit 1190–1205). With regard to the family’s possible roots in Hesse, it may have come from Gerhard of Dern (ca 1098), who was the same man as Gerhard of Hesse, a ministerialis of the Margraves of Meissen (floruit 1129–1149). Thus it seems that Johannes Sinapius’ concept that the Dera family came from the Dern family of Hesse can be proven
Keywords: Dehrn (rodzina); Doliwa (herb); rody; rycerstwo; Miśnia (Niemcy)